2016
DOI: 10.3727/096368916x692645
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Effects of Human Amniotic Membrane Transplantation in Established Biliary Fibrosis Induced in Rats

Abstract: Liver fibrosis is characterized by excessive accumulation of extracellular matrix components in the liver parenchyma that distorts the normal architecture and hepatic function. Progressive fibrosis could end in the advanced stage known as cirrhosis, resulting in the need to resort to liver transplantation. Amniotic membrane (AM) has emerged as an innovative therapeutic approach for chronic liver diseases due to its anti-inflammatory, antiscarring, and wound-healing effects. We have recently shown that AM can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
(78 reference statements)
1
33
0
2
Order By: Relevance
“…This hypothesis is supported by studies about hepatic fi brosis and its reversibility (Bataller and Brenner 2005, Kisseleva et al 2012, Sun and Kisseleva 2015, which have demonstrated that the mechanism of liver fi brosis regression is characterized fi rst by the decreased inflammatory and fibrogenic cytokine levels, increased collagenase activity, that degrade eCm, and then the disappearance of myofibroblasts. Consistent with these studies, Sant'Anna et al (2016) showed that the livers treated with Am had a 62% reduction in the main profibrotic cytokine, TGF-β1, when compared to the untreated group Bdl. Indeed, manuelpillai et al (2010) observed the decreased expression of TGF-β1 coupled with an induction of collagen-degrading metalloproteinases, and a reduction of their tissue inhibitors of metalloproteinases, thus, reducing the progression of fi brosis to advanced stages.…”
Section: Discussionsupporting
confidence: 73%
“…This hypothesis is supported by studies about hepatic fi brosis and its reversibility (Bataller and Brenner 2005, Kisseleva et al 2012, Sun and Kisseleva 2015, which have demonstrated that the mechanism of liver fi brosis regression is characterized fi rst by the decreased inflammatory and fibrogenic cytokine levels, increased collagenase activity, that degrade eCm, and then the disappearance of myofibroblasts. Consistent with these studies, Sant'Anna et al (2016) showed that the livers treated with Am had a 62% reduction in the main profibrotic cytokine, TGF-β1, when compared to the untreated group Bdl. Indeed, manuelpillai et al (2010) observed the decreased expression of TGF-β1 coupled with an induction of collagen-degrading metalloproteinases, and a reduction of their tissue inhibitors of metalloproteinases, thus, reducing the progression of fi brosis to advanced stages.…”
Section: Discussionsupporting
confidence: 73%
“…The benefits of placental membranes, amnion, and chorion, for the management of burns and chronic wounds, have been extensively outlined in the literature . Fresh placental membrane is inherently anti‐inflammatory, antimicrobial, and antifibrotic . When used as a wound cover, placental membranes maintain a moist environment in the wound, reduce pain, and support angiogenesis, granulation of the wound bed, and wound epithelialization .…”
Section: Discussionmentioning
confidence: 99%
“…9 Fresh placental membrane is inherently anti-inflammatory, antimicrobial, and antifibrotic. [10][11][12] When used as a wound cover, placental membranes maintain a moist environment in the wound, reduce pain, and support angiogenesis, granulation of the wound bed, and wound epithelialization. 13,14 Development of different tissue preservation methods have led to the commercialization of placental membranes; however, the majority of these preservation methods destroy viable tissue cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the amount of TGF-β in the hepatic tissue has been used to explain part of the mechanism of fibrosis reduction observed in other therapies such as administration of curcumin (38), chromium (17), and artemisia herb (39). Indeed, the recent study published by Sant'Anna et al (40) confirmed that AM applied to the liver after 2 weeks of BDL reduces the expression of TGF-β to about 62% compared to untreated controls.…”
Section: Discussionmentioning
confidence: 90%